Implementação do direito de participação das crianças em contexto de jardim de infância: As perceções dos educadores - Lopes, Luísa; Correia, Nadine; Aguiar, Cecília (Revista Portuguesa de Educação, 2016)
Com este estudo, pretendeu-se desenvolver e avaliar as características psicométricas de uma medida de avaliação das perceções dos educadores de infância acerca da implementação do direito de participação em contexto de jardim de infância. Participaram 168 educadores de infância, sendo que, destes, 40 foram observados, em contexto de sala, com o Classroom Observation Scoring System (Pianta, La Paro, & Hamre, 2008). Identificámos dois componentes das perceções dos educadores acerca da participação das crianças: Expressão e Responsabilidade das Crianças e Tomada de Decisão pelo Adulto. A Tomada de Decisão pelo Adulto estava negativamente associada à qualidade das salas e às habilitações académicas dos educadores. Paralelamente, educadores do setor público obtiveram resultados mais elevados no componente Expressão e Responsabilidade das Crianças do que educadores do setor privado com fins lucrativos. Os dados obtidos fornecem evidências que suportam, moderadamente, a fidelidade e a validade da medida. Palavras-chave: direito de participação das crianças, questionário, perceções, jardim de infância ABSTRACT The aim of this study was to develop and evaluate the psychometric properties of a measure designed to assess early childhood education teachers’ perceptions about the degree of implementation of children’s participation right in early childhood education. Participated in this study 168 preschool teachers, 40 of which were simultaneously observed, in their classrooms, with the Classroom Observation Scoring System (CLASS; Pianta, La Paro, & Hamre, 2008). We identified two components of teachers’ perceptions of children’s participation: Children’s Expression and Responsibility and Decision Making by the Adult. Decision Making by the Adult was negatively associated with the domains of classroom quality measured through CLASS and with teachers education level. Teachers from public centers scored higher in Children’s Expression and Responsibility than teachers from private for-profit centers. Findings provide moderate evidence on the reliability and validity of the Assessment Questionnaire of Early Childhood Education Teachers’ Perceptions about Children’s Participation Right. Key-words: children’s participation right, questionnaire, teacher perceptions, early childhood education